Metagenomic Next-Generation Sequencing (mNGS) for the Timely Diagnosis of Carbapenem-Resistant Klebsiella pneumoniae in Leukemia Patients - Huan Tao; Fang Hua; Yingying Chen; Yongqian Jia (Case Reports in Infectious Diseases)
This report shows the contribution of metagenomic next-generation sequencing (mNGS) as an alternative to challenging diagnostic infection in immunosuppressed individuals. Herein, we report two leukemia patients who developed severe infections due to carbapenem-resistant Klebsiella pneumoniae (CrKP). The mNGS can be strongly recommended as an alternative investigation for patients who are at high risk of infection without positivity on body fluid culture. This can provide the opportunity for adequate therapy.